A Descriptive Cross-Sectional Study on the Incidence, Risk Factor and Outcome of Delirium in Surgical Patients in the Semi-Closed Intensive Care Unit - Keyal, Niraj Kumar; Singh, Sashi Ram; Sarraf, Pramod Kumar; Yadav, Umesh Kumar (Med Phoenix, 2022)
Introduction: There is a variation in risk factors and outcome of delirium in surgical patients in different studies. This study was conducted to determine the incidence, risk factors, and outcome of delirium in the surgical semiclosed intensive care unit in a developing country. Materials and Methods: This descriptive study was done in 82 patients of age≥18 years that underwent non-neurological surgery and admitted for more than 24 hours in a level three intensive care unit of medical college from January 10, 2021 to January 9, 2022. The whole sampling method was used in our study. The Confusion Assessment Method-ICU and Richmond Agitation Sedation Scale were used to diagnose delirium and sedation, respectively, along with a checklist to assess risk factors. All data was transferred to the excel sheet and transferred to a statistical package for the social sciences-16. Chi-square test and Fisher’s exact probability test were used to detect the difference between groups in the univariate analysis, as appropriate. The risk factors were analysed using binary logistic regression. Result: Of the 82 ICU admissions 28(34.1%) developed delirium. Hyperactive delirium was the most common motor subtype 12(42.8%). The mean duration of delirium was 4.69±5.06 days. Hypertension and alcohol were identified as risk factors for delirium. Delirious patients had a longer length of stay in the ICU (10.1 ±12.7 vs 5.1 ±4.2 days) with no impact on the duration of mechanical ventilation, mortality, reintubation, and unplanned extubation. Conclusion: Early recognition of risk factors for delirium in surgical patients can decrease the mortality and morbidity of surgical patients.